How One Teacher, Two Students with Visual Impairments, and a Three-year R & D Project Could Change How All Students Learn Science - Urquhart, Vicki (Journal of the American Academy of Special Education Professionals, 2012)
You probably recognize this standard definition of a comet: "a relatively small extraterrestrial body consisting of a frozen mass that travels around the sun in a highly elliptical orbit." Add an accompanying photograph or diagram, and students "get" what a comet is, right? Science textbook publishers expect students to understand science concepts by describing them using content-specific vocabulary, but for some students, that is a huge roadblock. A student who is blind or who has a visual impairment likely has never seen a comet, either in a night sky or in a photograph, and even when a teacher provides an additional colorful description about "fire balls" and "tails," it does not always help. How, then, do students with visual impairments learn scientific concepts? And, what can a science teacher do to ensure all students, including those with visual impairments, are learning? Seeking answers to these questions, two entities–McREL, an education research and development organization, and Edinboro University of Pennsylvania–partnered on a three-year collaboration to design, develop, and test resources for general education science teachers and teachers of students with visual impairments in grades 6-12. The result was a 3-part framework, "Visualizing Science with Adapted Curriculum Enhancements" (ACE). With a direction set, the developers recruited science teachers of students with visual impairments to participate in the study. Most teacher participants had no prior knowledge of how to address the needs of their students with visual impairments, but during the process, everyone learned. What follows is the story of a high school chemistry teacher who jumped into this project blindfolded, literally.